The Application of Artificial Intelligence in Islamic Law Discovery - Karimullah, Suud Sarim (Mutawasith: Jurnal Hukum Islam, 2023)
This study comprehensively explores using artificial intelligence (AI) to discover Islamic law. This study relies on literature study with literature analysis conducted in an integrative and comprehensive manner. The results of this study indicate that the use of artificial intelligence in the discovery of Islamic law provides deep and efficient analytical capabilities, enabling the identification of Islamic legal trends, agreements, and differences between schools. However, challenges arise regarding transparency, bias, and the role of humans in the decision-making process. To combat this, solid ethical guidelines and strict regulations are needed. Artificial intelligence also influences the development of Islamic law by assisting in adaptation to the modern context, bridging the gap between Islamic law and technology, and facilitating a more inclusive and global understanding of Islamic law. In this context, collaboration between Islamic jurists, computer scientists, and religious communities is critical to harnessing artificial intelligence's full potential in supporting relevant and responsive Islamic law in changing times.